2021
DOI: 10.7759/cureus.15057
|View full text |Cite
|
Sign up to set email alerts
|

Diaphragm and Lung Ultrasonography During Weaning From Mechanical Ventilation in Critically Ill Patients

Abstract: Aim: Optimum timing is crucial to avoid negative outcomes of weaning. We aimed to investigate predictive values of diaphragmatic thickening fraction (DTF), diaphragmatic excursion (DE), and anterolateral lung ultrasound (LUS) scores in extubation success and compare with rapid shallow breathing index (RSBI) in patients extubated under traditional parameters.Methods: Patients undergoing mechanical ventilation for >48 hours were included in the study. In patients planned for extubation, sonographic evaluations o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 30 publications
2
23
0
1
Order By: Relevance
“…The measures of diaphragmatic function comprise DE and DTF, and DE is mainly related to the inspiratory volume during the inspiratory phase, regardless of whether it depends on muscle workload or ventilator support [ 24 , 25 ]. DTF, also known as the “ejection fraction” of the diaphragm, reflects the active contraction ability of the diaphragm in the face of mechanical load [ 22 , 26 , 27 ]. In the present study, both DE and DTF exhibited a higher predictive value than the RSBI, which is in line with previous studies [ 22 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…The measures of diaphragmatic function comprise DE and DTF, and DE is mainly related to the inspiratory volume during the inspiratory phase, regardless of whether it depends on muscle workload or ventilator support [ 24 , 25 ]. DTF, also known as the “ejection fraction” of the diaphragm, reflects the active contraction ability of the diaphragm in the face of mechanical load [ 22 , 26 , 27 ]. In the present study, both DE and DTF exhibited a higher predictive value than the RSBI, which is in line with previous studies [ 22 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted by Gok et al [17] concluded that sonographic evaluations accompanied by an RSBI will increase extubation success in the weaning process. Weaning failure may be due to underlying lung pathologies such as pulmonary fibrosis, pulmonary hemorrhage, and diffuse pulmonary infiltrate and also weaning-induced pulmonary edema as a result of heart-lung interactions which may be diagnosed by echocardiographic assessment.…”
Section: Discussionmentioning
confidence: 99%
“…Among the sonographic values obtained in T-tube stages, it has a PPV of over 90% in determining extubation success, which is 27.5% for DTF and 64 breaths/minute/liter for RSBI. Using sonographic examinations accompanied by RSBI in Weaning increases success 26 . We found the DTF cut-off value to be 26%.…”
Section: Discussionmentioning
confidence: 99%